Ability of parents to recall the injuries of their young children. Issue 1 (3rd February 2005) - Cummings, P; Rivara, F P; Thompson, R S; Reid, R J
Abstract : Objective: To estimate the ability of parents to recall the injuries of their children. Design: Comparison of parent recall with computerized medical records. Setting: A health maintenance organization in Washington State during 2003. Subjects: Parents of children younger than 6 years. Main outcome measures: The ratio of recalled injuries to injuries in computerized data. Results: Telephone interviews were completed with a parent of 1672 young children who had computerized medical data for at least one injury in the last year. Counting the three most recent treated injuries, the 1672 children had 1896 separate new injuries in the year before interview and parents recalled 1150 of these: recall ratio 0.61 (95% confidence interval (CI) 0.58 to 0.63). The recall ratio decreased from 0.82 (95% CI 0.79 to 0.85) for injuries one day before interview to 0.37 (95% CI 0.32 to 0.40) at 365 days before interview. For 341 major injuries the recall ratio was 0.80 (95% CI 0.76 to 0.84), for 202 minor injuries treated in an emergency department or hospital it was 0.77 (95% CI 0.71 to 0.82), for 597 minor injuries treated in urgent care it was 0.70 (95% CI 0.65 to 0.73), and for 756 minor injuries treated in a clinic it was 0.43 (95% CI 0.39 to 0.47). Conclusions: Recall decreased with time. Recall was best for major injuries, intermediate for minor injuries treated in a hospital, emergency department, or urgent care center, and worst for minor injuries treated in a clinic.